The molecular basis of the associations between non-alcoholic fatty liver disease and colorectal cancer - Qiu, Ting; Hu, Weitao; Rao, Zilan; Fang, Taiyong (Frontiers in Genetics, 2022)
Background: Given the ongoing research on non-alcoholic fatty liver disease (NAFLD) and colorectal cancer (CRC), the number of studies suggesting a strong link between NAFLD and CRC is on the rise, while its underlying pathological mechanisms remain uncertain. This study aims to explore the shared genes and mechanisms and to reveal the molecular basis of the association between CRC and NAFLD through bioinformatics approaches. Methods: The Gene Expression Omnibus (GEO) dataset GSE89632 is downloaded for NAFLD cases and healthy controls. Additionally, the GSE4107 and GSE9348 datasets are obtained for CRC cases and healthy controls. Differentially expressed genes (DEGs) are obtained for NAFLD and CRC datasets, as well as shared genes between the two disorders. GO and KEGG enrichment analyses are further conducted. Subsequently, the STRING database and Cytoscape software are utilized to establish the PPI network and identify the hub genes. Then, co-expression analysis is performed using GeneMANIA. Finally, NetworkAnalyst is available as a means to construct a miRNA-gene regulatory network. Results: Under the threshold of FDR≤0.01, 151 common genes are obtained in NAFLD and CRC. Categorization of GO functions shows that DEGs are predominantly enriched in “response to hormone”, “inflammatory response”, and “DNA-binding transcription activator activity, RNA polymerase II-specificity”. The predominant KEGG pathways in DEGs are the “IL-17 signaling pathway” and “TNF signaling pathway”. Additionally, MYC, ATF3, PTGS2, JUN, FOS, EGR1, SERPINE1, CXCL1, FOSB, CXCR4, and CCL2 are identified as hub genes by the evaluation of 7 algorithms. With the construction of miRNA-gene networks, 4 miRNAs, including miR-335-5p, miR-155-5p, miR-26b-5p, and miR-124-3p, are predicted to be potential key miRNAs. Conclusion: This study identifies possible hub genes for the occurrence of CRC in the presence of NAFLD and discovers the interaction of miRNAs and hub genes predicted between the two diseases, providing a novel understanding of the molecular basis for the relevance of CRC and NAFLD, thus contributing to the development of new therapeutic strategies to combat NAFLD and CRC.